HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KEMAMPUAN KLIEN MENGONTROL HALUSINASI - Edy Mulyono (ITKES Wiyata Husada Samarinda, 2017)
Hallucinations as a mental illness that is found and treatment needs special attention , especially from the family . As a result of hallucinations is a risk of injuring oneself , others and the environment . This is caused because the client is under the hallucination asking him to do something beyond consciousness , where the client can not control his hallucinations . This study aims to determine the Family Support Relationships With Clients Ability Level Control Hallucinations in room Outpatient Mental Hospital of Atma Husada Mahakam Samarinda. Correlational Descriptive type of research , with cross sectional study design , study sample consisted of 78 respondents by means of sampling by using accidental sampling technique . The analysis used the statistical test Chi Square . The results of statistical test Chi Square with p value p value in 1000 and is therefore greater than the alpha value of 0.05 then Ho is accepted , it means that there is no relationship with the level of family support clients' ability to control hallucinations in the psychiatric hospital outpatient area atma husada Mahakam samarinda.